Enhanced model and fuzzy strategy of air to fuel ratio control for spark ignition engines - Jansri, Anurak; Sooraksa, Pitikhate (My University, 2012)
Various mathematical models for the air to fuel ratio and control for spark ignition (SI) engines have been proposed to satisfy technical specifications. This paper reveals an improvement of the mean value model (MVEM) and a simple yet effective nonlinear control to enhance the air to fuel regulator. The regulator is designed by using a discrete fuzzy PI algorithm, which provides easy tuning, robustness, and rapid development with a simple architecture. Effects on the dead time, exhausted delay, time-varying air flow and chaotic disturbance are also included. The computer simulation results show satisfactory performance based on standard evaluation criteria. The proposed model has a great potential for practical implementations. © 2011 Elsevier Ltd. All rights reserved.
Keywords: Air-fuel ratio; FOPDDT; Fuzzy control; Internal combustion; Nonlinear control